Enniatin B induces expression changes in the electron transport chain pathway related genes in lymphoblastic T-cell line. (November 2018) - Alonso-Garrido, M.; Escrivá, L.; Manyes, L.; Font, G.
Abstract: Enniatin B is a ionophoric and lipophilic mycotoxin which reaches the bloodstream and has the ability to penetrate into cellular membranes. The purpose of this study was to reveal changes in the gene expression profile caused by enniatin B in human Jurkat lymphoblastic T-cells after 24 h of exposure at 1.5, 3 and 5 μM by next generation sequencing. It was found that up to 27% of human genome expression levels were significantly altered (5750 genes for both down-regulation and up-regulation). In the three enniatin B concentrations studied 245 differentially expressed genes were found to be overlapped, 83 were down and 162 up-regulated. ConsensusPathDB analysis of over-representation of differentially expressed genes provided a list of gene ontology terms in which several biological processes related to nucleoside monophosphate metabolic process, respiratory chain complex, electron transport chain, oxidative phosphorylation and cellular respiration were the most altered. Also, an interesting correlation was found between enniatin B toxicity and the up-regulation of the UCP protein complex. In summary, the transcriptomic analysis revealed that mitochondria are the organelles showing more related differentially expressed genes. Consequently, differentially expressed genes involved in biological processes, molecular functions and pathways related to mitochondrial metabolism and respiration were significantly changed. Graphical abstract: Highlights: Mitochondria are the main organelles targeted showing the highest number of differentially expressed genes (DEGs). The number of DEGs involved in the poly(A) RNA binding molecular process was remarkably high. Enniatin B (EN B) induced perturbation in 36% of the respiratory chain genes. Electron transport chain pathway and oxidative phosphorylation pathway showed 23, 42 and 43 DEGs for 1.5, 3 and 5 μM. Uncoupling Protein-1 (UCP-1) was found to be up-regulated in treated cells.